2020
DOI: 10.1111/irv.12786
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the benefits of seasonal influenza vaccination: Elements of a framework to interpret estimates of vaccine effectiveness and support robust decision‐making and communication

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Among the European studies, eight (36.4%) were conducted specifically in Italy [ 3 , 4 , 13 , 31 , 38 , 39 , 43 , 47 ]. In addition, of the 40 articles included in our work, 17 (42.5%) were systematic reviews or literature reviews [ 3 , 5 , 10 , 11 , 12 , 22 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 37 , 41 , 47 , 48 ], ten (25%) were economic evaluations [ 8 , 13 , 19 , 21 , 23 , 26 , 27 , 34 , 44 , 45 ], seven (17.5%) were cross-sectional studies [ 18 , 35 , 36 , 38 , 42 , 43 , 49 ], two studies (5%) were HTA reports [ 4 , 39 ], one study (2.5%) was a nonlinear regression model [ 33 ], and three studies (7.5%) were expert opinions [ 20 , 40 , 46 ]. The main features of the studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHO's recommendation for northern and southern hemisphere influenza vaccine composition is predicted and introduced every year independently [71,72]. However, the vaccine's effectiveness is variable between seasons and depends on prediction accuracy [73]. Hence, it is important to create new and faster methods for vaccine production to increase vaccination efficiency.…”
Section: Nanotechnology In Vaccination Strategiesmentioning
confidence: 99%